2022
DOI: 10.1117/1.jbo.27.11.110501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resolution optoacoustic microscopy using a picosecond high repetition rate Q-switched microchip laser

Abstract: . Conventional optoacoustic microscopy (OAM) instruments have at their core a nanosecond pulse duration laser. If lasers with a shorter pulse duration are used, broader, higher frequency ultrasound waves are expected to be generated and as a result, the axial resolution of the instrument is improved. Here, we exploit the advantage offered by a picosecond duration pulse laser to enhance the axial resolution of an OAM instrument. In comparison to an instrument equipped with a 2-ns pulse duration laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…and Notsuka et al. improved axial resolution through novel laser sources 52 and adaptive optics, 53 respectively. Nteroli et al.…”
Section: Pa Plus Advanced Laser Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…and Notsuka et al. improved axial resolution through novel laser sources 52 and adaptive optics, 53 respectively. Nteroli et al.…”
Section: Pa Plus Advanced Laser Sourcesmentioning
confidence: 99%
“…Therefore, many research studies have focused on the improvement of resolution by innovating laser sources. Nteroli et al and Notsuka et al improved axial resolution through novel laser sources 52 and adaptive optics, 53 respectively. Nteroli et al showed that ultrafast picosecond excitation can generate ultrasound waves of a higher frequency for up to 50% improvement in axial resolution.…”
Section: Enhancing Resolutionmentioning
confidence: 99%